Advanced unsaturated soil mechanics and engineering - Ng Charles W. W. (Taylor & Francis, 2007)
Analytical and comprehensive, this state-of-the-art book examines the mechanics and engineering of unsaturated soils, as well as explaining the laboratory and field testing and research that are the logical basis of this modern approach to safe construction in these hazardous geomaterials; putting them into a logical framework for civil engineering and design.